Integration of biochemical and topographic cues for the formation and spatial distribution of invadosomes in nasopharyngeal epithelial cells. (1st January 2020) - Tsang, C.M.; Liu, Z.Y.; Zhang, W.; You, C.; Jones, G.E.; Tsao, S.W.; Pang, S.W.
Abstract: Invadosomes are invasive protrusions generated by cells which can secrete matrix metalloproteinases for focal digestion of extracellular matrix. They also aid invasive cancer cells in their transmigration through vascular endothelium. However, how the physical and chemical cues in a three-dimensional (3D) system signal the spatial localization of invadosomes remains largely unknown. Here we study the topographic guidance of invadosome formation in invasive nasopharyngeal cells under the stimulation of an inflammatory cytokine, TGF- β 1, using engineered gratings with different width and depth. We first report that TGF- β 1 can act as an external signal to upregulate the formation of invadosomes with a random distribution on a plane 2D surface. When the cells were seeded on parallel 3D gratings of 5 µm width and 1 µm depth, most of the invadosomes aligned to the edges of the gratings, indicating a topographic cue to the control of invadosome localization. While the number of invadosomes per cell were not upregulated when the cells were seeded on 3D topography, guidance of invadosomes localization to edges is correlated with cell migration directionality on 1 µm deep gratings. Invadosomes preferentially form at edges when the cells move at a lower speed and are guided along narrow gratings. The invadosomes forming at 3D edges also have a longer half-life than those forming on a plane surface. These data suggest that there are integrated biochemical and 3D geometric cues underlying the spatial regulation of invasive structures so as to elicit efficient invasion or metastasis of cells. Statement of significance: Nasopharyngeal cells were integrated with the biological cues and matrix topography to govern the activity and spatial distribution of invadosomes. The biochemical induction of invadosome formation by TGF-β1 in nasopharyngeal cells was observed. When the cells were seeded on parallel 3D gratings, most of the invadosomes aligned to the edges of the gratings due to topographical induced invadosome localization. While the number of invadosomes per cell were not upregulated, guidance of invadosomes localization to edges is correlated with cell migration directionality on 1 µm deep gratings. Invadosomes preferentially form at edges with a higher stability when the cells are guided along narrow gratings. The integrated biochemical and 3D geometric cues could elicit efficient invasion or metastasis of cells. Graphical abstract: Image, graphical abstract